Pengaruh Pemahaman dan Tingkat Kepercayaan Masyarakat terhadap Rendahnya Inklusi Keuangan Warga Kota Medan dalam Penggunaan Mobile Banking di Era Cashless Society - Dewi, Nurul Aulia; Siregar, Tetty Handayani; Muda, Iskandar; Soemitra, Andri; Soemitra, Yusrizal (JSE: Jurnal Sharia Economica, 2025)
This study aims to analyze the influence of public Understanding and Trust on the low Financial Inclusion of Medan City residents in using mobile banking in the cashless society era. A quantitative approach was employed, using a survey technique with questionnaires distributed to 100 randomly selected respondents based on the Slovin formula. Data were analyzed using SmartPLS 4.0, with validity, reliability, and path analysis tests. The results reveal that public Understanding (digital financial literacy) and Trust significantly and positively influence Financial Inclusion through mobile banking adoption in Medan City. Despite improvements in technological infrastructure and access, challenges remain in user knowledge and trust in financial technology. Public Understanding, which encompasses both technical use and the ability to make informed financial decisions, was found to be a key determinant. Trust in digital financial services, influenced by factors such as data security, transaction clarity, and transparency, also plays a crucial role in encouraging mobile banking use. Statistical analysis indicates that these variables explain 48.8% of the variation in Financial Inclusion, aligning with the Technology Acceptance Model (TAM) and Trust-Based Acceptance Model (TBAM), as well as previous studies